Depósitos estaníferos e técnicas de pesquisa e prospecção: exemplo do depósito de SN da Faixa Placha, província estanífera de Goiás, Brasil - BONFIM, Luís Antônio Raposo (2019)
The massive granite Pedra Branca is located in the Tin Province of Goiás, located on the Tocantins Structural Province, Central Brazil, the central portion of the South American platform. The study of this massive was intended to provide a deposit model and exploration strategy, aimed at detecting Sn mineralization associated with granitic plutons. Studies on the geological, geochemical and metallogenetic observed in this deposit and compared the major Brazilian tin provinces was the basis for this work. The methodology used corresponded to the interactive analysis of thematic maps that considered factors such as geology, geochemistry, geophysics and metallogenic concepts and fields of valuation techniques (trenches and drilling), enabling the display and location of mineralized deposits of tin. Such integration methodology can be applied to finding mineralization Sn related to granitic plutons which is the case of Placha range, located in the massive granite white stone. There was detected primary mineralization of tin 15.000t order contained in one track only 1.5 km long, meaning that all potential Placha range can be tripled if deemed its extension over 5km long, addition of secondary deposits that are formed by relatively shallow alluvium and small waste material thickness distributed over large areas.